Manajemen Komunikasi Pemasaran Perusahaan Coffee Shop pada Era New Normal - Aulia Muhammad; Mochammad Rochim (UNISBA Press, 2023)
Abstract. The Covid 19 pandemic has had an impact on the management of the coffee shop business. Many coffee shops have been hit in running their business (collapsed), and many have even died. On the other hand, coffee shop managers are also faced with increasing competition from coffee shops. This research focuses on how the management of marketing communications for coffee shop companies in the new normal era. The aim of the study was to determine marketing communication management for the Bandung Kilogram coffee shop which includes planning, organizing, acting , and controlling in the New Normal era. This study used a qualitative research method with a case study approach. The results of the study show that Kilogram Coffee Shop's marketing communication management in the new normal era is: 1) planning is carried out by encouraging all company programs in offline (face-to-face) and online forms and using endorsements to convey messages to customers and to maintain good relations with customers is done by face to face communication , giving promotions, and holding more offline events and involving the community; 2) organizing ( organizing ) was carried out by changing the organizational structure and adding new divisions, namely Holding, Operations Manager, Marketing Division, and separating the Finance Division which was previously concurrently held by the Operations Manager during the pandemic era ; 3) Actuating is done by adding more offline events and involving the community. Sales are carried out offline and online with the help of market place. The delivery of messages (publications) to customers is carried out by adding new methods, namely involving endorsements, and 4) control is carried out by all employees, starting from Holding, General Manager, Operations Manager, Leaders of each Division, to staff. The supervision of online publications is carried out by the Marketing and Program Division. Abstrak. Pandemi Covid 19 berdampak pada pengelolaan usaha coffee shop. Banyak coffee shop yang terpukul dalam menjalankan usahanya (colaps), bahkan banyak pula yang mati. Di sisi lain, pengelola coffe shop juga dihadapkan pada persaingan coffe shop yang jumlahnya terus bertambah. Penelitian ini berfokus pada bagaimana manajemen komunikasi pemasaran perusahaan coffee shop pada era new normal. Tujuan penelitian untuk mengetahui manajemen komunikasi pemasaran coffee shop Kilogram Bandung yang meliputi perencanaan (planning, pengorganisasian (organizing), pelaksanaan (actuiting), dan pengawasan (controlling) pada era New Normal. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Hasil penelitian menunjukkan, manajemen komunikasi pemasaran Kilogram Coffee Shop pada era new normal adalah: 1) perencanaan (planning) dilakukan dengan mendorong semua program perusahaan dalam bentuk offline (tatap muka) dan online serta menggunakan endorsement untuk menyampaikan pesan kepada pelanggan dan untuk menjaga hubungan baik dengan pelanggan dilakukan dengan komunikasi face to face, memberikan promosi-promosi, dan menyelenggarakan event offline yang lebih banyak dan melibatkan komunitas; 2) pengorganisasian (organizing) dilakukan dengan mengubah struktur organisasi dan menambah divisi baru yaitu Holding, Manager Operasional, Divisi Marketing, dan memisahkan Divisi Finance yang sebelumnya dirangkap oleh Manager Operasional pada era pandemi; 3) pelaksanaan (actuating) dilakukan dengan menambah event offline yang lebih banyak dan melibatkan komunitas. Penjualan dilakukan offline dan online dibantu market place. Pelaksanaan penyampaian pesan (publikasi) kepada customers dilakukan dengan menambah cara baru yaitu melibatkan endorsement, dan 4) pengawasan (controlling) dilakukan oleh semua karyawan, mulai dari Holding, General Manager, Manajer Operasional, para Leader tiap Divisi, sampai ke staff. Untuk pengawasan publikasi online dilakukan oleh Divisi Marketing dan Program.